TP5.2.5 The utility of 'kissing' common iliac artery stents in the management of occlusive atherosclerotic arterial disease of the aortic bifurcation. (28th October 2021) - Delaney, Jenna; Templeman, Joshua; Hussey, Keith
Abstract: Introduction: A systematic review published in 2017 concluded that 'kissing' iliac stents to treat occlusive disease of the aortic bifurcation was associated with high technical procedural success and good medium-term patency. We have explored this in a regional vascular unit. Methods: Retrospective review of patients managed with endovascular treatment of aorto-iliac segment (March 2015 to September 2020). The median follow-up was 2-years. Key outcome variables included the patency of the reconstruction and requirement for secondary intervention. Results: There were 1, 348 iliac endovascular procedures performed for occlusive atherosclerotic arterial disease of the aorto-iliac segment of which 56 were 'kissing' iliac stents. Intervention was performed for chronic limb threatening ischaemia in 29 cases. In 37 cases patients had unilateral symptoms only and in 41 cases patients had either TASC A or B lesions. Technical success was achieved in 55 cases and the median duration of admission was 1-day. At follow-up there was clinical patency in 54 cases, although there were 3 major extremity amputations performed (all on the index admission). Conclusion: As with much of the work on 'kissing' iliac stents the number of patients is small and the group of patients variable in terms of medical co-morbidity, presenting clinical features and morphology of iliac disease. The procedure appears to have high technical success and can be achieved with little in the way of major morbidity. Medium term durability is good.